Building national emission inventories of toxic pollutants in Europe - Leclerc, Alexandra; Sala, Serenella; Secchi, Michela; Laurent, Alexis (Environment international, 2019)
The reduction of chemical pollution is a priority in many regional, national, and international policies, including in EU countries. To effectively do so, quantified overviews of pollutant emissions at national levels and with some granularity in their sources, are required. However, current monitoring efforts are often scattered and a quantitative and comprehensive inventory of toxic emissions in Europe is lacking. Toxic pollutants stem from a large variety of emission sources from industry, agriculture, households, etc. and the difficulty to cover all of them is manifest in public databases and official reports, where data gaps across countries and years exist for several substances. Here, we propose a methodology to tackle this problem and build comprehensive and harmonized national inventories of toxic pollutants. Using public databases, official reports, scientific literature and developing extrapolation techniques specific to each emission source, we derived harmonized annual inventories of toxic pollutants in all EU Member States over the years 2000–2014. They present an unprecedented coverage of 805, 572, and 468 substances emitted to air, water and soil, respectively. Although the resulting dataset shows a relatively good agreement with previous inventories of narrower scopes, uncertainties can be identified for specific emission sources and in the development of extrapolation techniques, thus calling for further research in these areas. Such efforts should also explore adaptation of the methodology to derive comprehensive inventories for countries outside EU, where data is scarcer. Nonetheless, the developed national inventories can provide a starting point for territorial chemical footprints of toxic pollutants and could be coupled with environmental impact assessment for gauging the damages to ecosystems and human health from toxic pollutants emitted in Europe. This can ultimately support policy-makers in their pollutants prioritisation and benchmarking across substances and countries towards improved toxic emission reduction policies. •We developed harmonized national inventories of toxic emissions in EU over 2000–2014.•Unprecedented coverage of 805, 572, & 468 substances to air, water, and soil was reached.•Completeness and accuracy of official reports are critical for overall uncertainty.•The developed inventories can be starting points for nations' chemical footprints.•With impact assessment, they can support holistic prioritisation and benchmarking.